Keberlanjutan collaborative reflection berbasis mediasi keluarga: sebuah model pendidikan karakter di lingkungan preschool daycare - Lutfiah Nur Azizah; Asep Kurnia Jayadinata; Dhea Ardiyanti (Indonesian Institute For Counseling, Education and Therapy, 2026)
The study aims to comprehensively analyse the role of the family environment in perpetuating the values of Collaborative Reflection as a character education strategy in daycare centers to maximize the development of children’s character. The study was conducted at Jagad Solution Daycare with 9 parents of daycare children and 3 teachers as participants. The research method use was a qualitative approach with an exploratory design. Data collection was conducted through semi structured interviews, non participant observations, documentation and a survey as supporting data. Data analysis was conducted by applying the Miles and Huberman analysis model, which includes data collection, data reduction, data presentation and drawing conclusions. The results of study indicate that the role of the family environment in maximizing the sustainability of Collaborative Reflection practices at the daycare has a positive impact on enhancing children’s character development. However, in reality, parents still face challenges in optimizing the role of the family environment in character based learning. These findings also indicate that, despite the obstacles to implementation, parents and teachers consistently strive to guide, support and foster open communication in creating a supportive family environment to strengthen children’s character.